Penggunaan Analisis Video Gerak Kucing Melompat Berbantuan Aplikasi Tracker Sebagai Kegiatan Praktikum Mandiri Materi Gerak pada Peserta Didik SMP - Desi Ramadhanti*; Heru Kuswanto; Hestiana Hestiana; Aisha Azalia (Universitas Syiah Kuala, 2021)
The Covid-19 pandemic has impacted various fields, especially education, namely the implementation of distance learning. One of the activities carried out by teachers is the implementation of independent practicum by students so that teaching and learning activities continue to run even though the students are at home. This study aims to analyze the motion of jumping cats using a tracker application that can be used as a practicum activity independently in science subjects of motion material in grade VII by using cats that are in the environment of learners as the subject of the study. This research method uses a hands-on experimental approach by taking videos of jumping cats' motion and processing them with a tracker app. The results of data processing with the help of tracker application are processed by using Microsoft Excel program so that obtained KD, KB, TB, K and E relationship graphs cat jump has a constant or stable speed indicated by linearity graphs. In addition, data processing using a tracker application is more accurate and consistent compared to the acceleration value by manually calculating so that it can be concluded the use of application-assisted jumping cat video analysis is worth using in science learning.